Permanence for a Delayed Nonautonomous SIR Epidemic Model with Density-Dependent Birth Rate - Li Yingke; Chen Liang; Wang Kai (Discrete Dynamics in Nature and Society)
Based on some well-known SIR models, a revised nonautonomous SIR epidemic model with distributed delay and density-dependent birth rate was considered. Applying some classical analysis techniques for ordinary differential equations and the method proposed by Wang (2002), the threshold value for the permanence and extinction of the model was obtained.